(untitled) (Research, Society and Development, 2022)
The use of nickel-titanium alloys revolutionized endodontics and made endodontic treatments even more effective, as they caused less changes in the original anatomy of the root canal. With the emergence of new automated systems such as Reciproc® (VDW GmbH, Munique, Alemanha) and Wave One® (Dentsply-Mailefer, Ballaigues, Suíça), these systems soon became known in the market for presenting an improved NiTi alloy called M-Wire, which increased the flexibility and resistance of these instruments. This study aims to evaluate the characteristics of reciprocating RECIPROC® (VDW GmbH, Munich, Germany) and WAVE ONE® (Dentsply-Mailefer, Ballaigues, Switzerland) files through a literature review. A bibliographic survey was carried out in the following databases: BVS, Lilacs, Pubmed. The inclusion criteria were articles in full, in Portuguese and English and which were published from 2012 to 2021. It was concluded that the oscillatory systems researched showed promise, but more studies are yet to be carried out to assess the performance of both, as newer and improved versions of these instruments have been released onto the market.